Conversion of methane to gasoline range hydrocarbons over W/HZSM-5 catalyst: effect of co-feeding - Kusmiyati, Kusmiyati; Saidina Amin, Nor Aishah (2007)

(untitled)
The conversion of methane in the presence of co-feedings into hydrocarbons in gasoline range over W/HZSM-5 catalyst has been studied in a fixed bed reactor at atmospheric pressure. The effect of CH4/C2H4 ratio in the methane and ethylene feed shows that the fraction of gasoline hydrocarbon (C5+ aliphatics and aromatics) in the product distributions increased with high ethylene concentration. The effect of loading W into HZSM-5 catalyst for the conversion of methane and ethylene (ratio CH4/C2H4=86/14) shows that W/HZSM-5 has higher conversion and higher resistance towards deactivation than that on HZSM-5. The influence of temperatures (between 250-450Â°C) on the conversion of methane and ethylene feed shows that increasing temperature, the selectivity to aromatic products increased. In addition, the conversion of methane with co-feeding of methanol and mixtures of ethylene and methanol were also studied. The result shows that the production of C5+ aliphatics increase with the introduction of ethylene and methanol into the methane feed.